Enhancing nutritional knowledge and practices: The impact of nutrition education on iron and calcium consumption among cricket players - Jauhari, Mansur; Sukur, Abdul; Jayanti, Linda Dwi (Journal Sport Area, 2024)
Background Problems: This study emphasises the critical importance of maintaining a balanced intake of nutrients relative to individual needs, as deficiencies or excesses can significantly impact health and nutritional status. Among these essential nutrients are iron and calcium. Research Objectives: The aim of this research is to assess the impact of nutrition education on the knowledge and dietary practices related to iron and calcium among athletes. Methods: The research used a pre-experimental design with a one-group pretest-posttest. To evaluate the effect of the intervention, the subjects were given a pretest, nutrition education, and posttest. The study was conducted on a total of 30 cricket players from the Special Capital Region of Jakarta over a period of 1 month, with a frequency of 4 intervention meetings, each session lasting 60 minutes. Data analysis was performed using an independent t-test. The participants in this research were cricket players from Jakarta. Findings and Results: The results indicated that nutrition education significantly improved athletes' nutritional knowledge (p-value 0.000) and dietary practices (p-value 0.011). Conclusion: This research demonstrates the effectiveness of targeted nutrition education interventions in enhancing athletes' knowledge and adoption of healthier dietary practices, particularly concerning iron and calcium consumption. These findings contribute valuable insights to the field of sports nutrition, emphasising the importance of well-designed educational programs in promoting good nutritional behaviour and supporting overall health and performance in athletes. This study underscores the critical role of nutrition education in the advancement of both the scientific understanding and practical application of sports nutrition.